2018
DOI: 10.1080/03639045.2017.1421662
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles obtained by confined impinging jet mixer: poly(lactide-co-glycolide) vs. Poly-ε-caprolactone

Abstract: This paper is focused on the production and characterization of polymeric nanoparticles obtained by nanoprecipitation. The method consisted of using a confined impinging jet mixer (CIJM), circumventing high-energy equipment. Differences between the use of poly-ε-caprolactone (PCL) and poly(lactide-co-glycolide) (PLGA) as concerns particle mean size, zeta potential, and broad-spectrum antibiotic florfenicol entrapment were investigated. Other analyzed variables were polymer concentration, solvent, and anti-solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Below this critical mixing threshold BCP concentration has a limited effect on controlling NP size . For nonamphiphilic polymers, NP radius is found to be proportional to concentration of the polymer in the solvent stream with an exponent of ≈ 1 / 3 , meaning the number of polymers per NP is directly proportional to the concentration. , This is well in agreement with other nanoprecipitation studies, in the absence of turbulent-like mixing. , One would also expect, given the size-mass dependence of a polymer chain R ∝ N ν where N is the degree of polymerization and ν is the Flory exponent, that larger molecular weights would result in larger NPs. There is some evidence of larger molecular weight leading to larger NPs. , However, these conclusions have not yet been universally extended across a wider range of polymeric systems with FNP.…”
Section: Polymeric Np Formation By Flash Nanoprecipitation (Fnp)supporting
confidence: 86%
See 1 more Smart Citation
“…Below this critical mixing threshold BCP concentration has a limited effect on controlling NP size . For nonamphiphilic polymers, NP radius is found to be proportional to concentration of the polymer in the solvent stream with an exponent of ≈ 1 / 3 , meaning the number of polymers per NP is directly proportional to the concentration. , This is well in agreement with other nanoprecipitation studies, in the absence of turbulent-like mixing. , One would also expect, given the size-mass dependence of a polymer chain R ∝ N ν where N is the degree of polymerization and ν is the Flory exponent, that larger molecular weights would result in larger NPs. There is some evidence of larger molecular weight leading to larger NPs. , However, these conclusions have not yet been universally extended across a wider range of polymeric systems with FNP.…”
Section: Polymeric Np Formation By Flash Nanoprecipitation (Fnp)supporting
confidence: 86%
“…FNP from numerous biocompatible polymers with these solvent combinations have been reported; e.g. , PEG- b -PLA in THF/DMSO mixtures, acetone or DMF, and PCL or poly­(lactic- co -glycolic acid) (PGLA) in acetone, , as well as acetonitrile/sodium chloride solution with acetylated carboxymethylcellulose (Cellax) functionalized with poly­(ethylene glycol) (PEG) and a hydrophobic drug moiety …”
Section: Polymeric Np Formation By Flash Nanoprecipitation (Fnp)mentioning
confidence: 99%
“…Many researchers have used this CIJM to prepare various drug nanoparticles summarized in Table 1 . They were mainly applied in the preparation of drug polymeric micelles 42 , 43 , 44 , 46 , 47 , 50 , polymeric nanoparticles 88 , 89 , 90 and solid lipid nanoparticle 48 , 49 , 91 by nanoprecipitation methods. The high mixing efficiency and uniformity via CIJM were helpful in creating high supersaturation and high nucleation rates, which generated small and uniform nanoparticles with higher drug encapsulation efficiency (DEE) and drug loading capacity (DLC).…”
Section: Mixing Devicesmentioning
confidence: 99%
“…As mentioned in the principle of FNP, the increasing in the flow rates of the opposite liquid jets will contribute to the higher supersaturation levels and thus higher nucleation rates, which generate smaller and uniform nanoparticles. Turino et al 88 prepared PCL and PLGA nanoparticles with different particle size at different flow rates from 40 to 120 mL/min. Their study showed the higher velocity of the two opposite streams, the smaller nanoparticles obtained.…”
Section: Mixing Devicesmentioning
confidence: 99%
“…Pinto et al . reported lower entrapments and efficiencies values using the emulsion solvent diffusion–evaporation method for the preparation of FF‐PLGA nanoparticles, while Turino et al . obtained similar entrapments but lower efficiencies values when nanoparticles were prepared using the nanoprecipitation method.…”
Section: Resultsmentioning
confidence: 99%